Factors Caused Difficulty in Learning Science for Students - Siska Novianti; Liza Yulia Sari; Aulia Afza (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
This research is motivated by the problems found in class in terms of internal and external factors. Internal factors include that students are not motivated to learn they prefer to play games than repeat lessons, then many students are not interested in learning science. On external factors, namely learning facilities are not yet complete such as the unavailability of school laboratories so that the learning process is less effective. This results in low learning outcomes obtained by students. This study aims to determine the factors that cause learning difficulties in science for seventh grade students viewed from internal and external factors. This type of research is descriptive qualitative research. All members of the population were used as research samples using total sampling technique. The instrument used in this study was a questionnaire consisting of 71 statement items. From the results of the study, it can be concluded that the internal factors that most influence students' learning difficulties are physical factors with a percentage of 50.44% (difficult), while the external factors that most influence students' learning difficulties are community factors with a percentage of 55.13 % (difficult), so that the overall average learning difficulties of class in science learning are 58.85% (difficult).